The Relationship of Lactate Albumin Ratio With Sofa Score As A Predictor of Sepsis Patients in The Intensive Care Room - Karim, Tengku Abdul; Hanafie, Achsanuddin; Tanjung, Qadri Fauzi; Amelia, Rina (Syntax Corporation Indonesia, 2025)
Sepsis is a life-threatening organ dysfunction due to dysregulation of the host response to infection which causes systemic changes, namely an increase in the serum lactate/albumin ratio which is associated with mortality. Method:This study is a clinical observational analytical study with a prospective cohort design at fittingAdult patients diagnosed with sepsis in the integrated inpatient ward and intensive care ward at Haji Adam Malik General Hospital, Medan. The subject sampling technique used was non-probability sampling with a consecutive sampling method where 50 subjects were required. Bivariate analysis used the Pearson correlation test and the linear relationship between the lactate-albumin ratio value and the SOFA score used linear regression. A 95% confidence interval with a p value <0.05 was considered significantly significant Results :The results of the research on the first day found that the average LAR H1 was 0.59 + 0.51 (0.12-2.26) and the average SOFA H1 score was 7.32 + 1.88 (7) where an r value of 0.726 was obtained. indicates a high and significant correlation between Lactate Albumin Ratio and SOFA Score as a predictor of sepsis patients (p value = 0.000, p<0.05). On the third day, the average LAR H3 score was 0.12 + 0.29 (0.21-0.47) and the average SOFA H3 score was 9.58 + 2.01 (10) where an r value of 0.33 was found which indicates Very low and insignificant correlation between Lactate Albumin Ratio and SOFA Score as a predictor of sepsis patients (p value = 0.818, p > 0.05). Conclusion:The lactate-albumin ratio was strongly correlated with the SOFA score on the first day of adult patients diagnosed with sepsis in the integrated inpatient ward and intensive care ward.